2023
DOI: 10.1002/fsn3.3340
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effects of palm kernel meal feeding on the meat quality and rumen microorganisms of Qinghai Tibetan sheep

Abstract: Palm kernel meal (PKM) has been shown to be a high‐quality protein source in ruminant feeds. This study focused on the effects of feed, supplemented with different amounts of PKM (ZL‐0 as blank group, and ZL‐15, ZL‐18, and ZL‐21 as treatment group), on the quality and flavor profile of Tibetan sheep meat. Furthermore, the deposition of beneficial metabolites in Tibetan sheep and the composition of rumen microorganisms on underlying regulatory mechanisms of meat quality were studied based on ultra‐performance l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…An UHPLC (1290 Infinity LC, Agilent Technologies), coupled to a quadrupole TOF (AB Sciex Triple TOF 6600), was used for the analysis. The conditions for HILIC separation and the ESI source were set as previously described ( Ma, Han, Raza, et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…An UHPLC (1290 Infinity LC, Agilent Technologies), coupled to a quadrupole TOF (AB Sciex Triple TOF 6600), was used for the analysis. The conditions for HILIC separation and the ESI source were set as previously described ( Ma, Han, Raza, et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…For example, TMR containing palm kernel meal at 18% of Tibetan sheep increased the abundance of Christensenellaceae R-7, Ruminococcaceae UCG-013, Lachnospiraceae UCG-002, and Family XIII AD3011 in the rumen but decreased the abundance of Prevotella www.nature.com/scientificreports/ the above bacteria groups regulate meat quality by regulating rumen metabolites (succinic acid, DL-glutamic acid, etc.) 38 . In this study, RL2, RL3 and RL4 decreased the abundance of Prevotellaceae UCG001 compared with RL1.…”
Section: Effects Of Fermented Feed On the Structure Of Rumen Bacteria...mentioning
confidence: 99%
“…Studies from Ding and Burrin showed that adding amino acids to animal diets can provide energy for the small intestine, increase the abundance of intestinal microbiota as well as maintain intestinal integrity ( Burrin and Reeds, 1997 ; Ding et al, 2019 ). In this context, studies by Ma et al (2023) revealed that feed additives could influence muscle metabolites and improve meat quality by altering the composition of rumen microorganisms in Tibetan sheep. In a similar vein, Zhiwei ( Zhao et al, 2021 ) found that supplementing the diet of lactating yaks with RPMET and RPLYS could alter the composition of their rumen bacteria, influence the rumen fermentation environment and metabolism and ultimately alter the synthesis of metabolites in milk.…”
Section: Introductionmentioning
confidence: 99%